A Group Theory Approach towards Some Rational Difference Equations. (1st December 2019) - Folly-Gbetoula, Mensah; Mnguni, Nkosingiphile; Kara, A. H.
Abstract : A full Lie point symmetry analysis of rational difference equations is performed. Nontrivial symmetries are derived, and exact solutions using these symmetries are obtained.